Implementasi Penggunaan Lembar Kerja Peserta Didik (LKPD) Kelas IV SD Negeri 275/Vi Bungo Tanjung III - Shinta Isnaini Syafa’atin; Titik Ratnasari; Syahrial Syahrial; Silvina Noviyanti (AS-SABIQUN, 2022)
One of the learning tools that can be used is the Student Worksheet or often referred to as LKPD. In addition, LKPD also plays a role in helping teachers in directing students to find concepts through their own activities. With the LKPD, students are expected to be able to carry out learning activities and express their creative ideas both individually and in groups, able to think critically and establish good cooperation with group members. This research uses a qualitative approach with the type of case study with the subject being the fourth grade teacher at SDN 275/VI Bungo Tanjung III. In collecting data, researchers used the methods of observation, interviews, and documentation. The data analysis technique used is data reduction, data display, and drawing conclusions. To test the validity of the data used triangulation method. Based on the data from research results in class IV, it is known that there are several applications in the use of LKPD in the learning process such as making it easier for students to interact with the material provided, presenting tasks that increase students' understanding of the material provided, training students' learning independence, and make it easier for teachers to give assignments to students. Based on the results of research and discussion, it can be concluded that the implementation of the use of student worksheets for class IV SD Negeri 275/VI Bungo Tanjung III is in accordance with teaching materials and can be seen on the student activity sheets including: Title LKPD, Introduction, Activity Objectives, Tools and materials, Activity Steps, Tables/observations, Questions, Conclusions.